Burden of road traffic accidents in Nepal by calculating disability-adjusted life years. Issue 3 (1st October 2017) - Huang, Ling; Poudyal, Amod K.; Wang, Nanping; Maharjan, Ramesh K.; Adhikary, Krishna P.; Onta, Sharad R.
Abstract : Objective: To calculate the burden of road traffic accidents in Kathmandu Valley and then extrapolate this to the national level. Methods: A prospective study was performed to compute the burden of road traffic accidents by quantification of disability-adjusted life years (DALYs) using the Global Burden of Disease Study method on the basis of 1-year data from nine hospitals in Nepal and the Department of Forensic Medicine and cross-checked with the Nepal Traffic Directorate. Multiple methods were applied to the extrapolated population metrics of the burden of road traffic accidents in Nepal. Results: The total number of years of life lived in disability, years of life lost, and DALYs in Nepal were 38, 848±194, 119, 935±1464, and 158, 783±1658 (95% confidence interval) respectively. The number of years lost because of morbidity and death was similar in Kathmandu Valley. Most (75%) of the DALYs resulted from years of life lost in Nepal. Males accounted for 73% of DALYs. Almost half (44%) of the DALYs were contributed by the group aged 15–29 years. Conclusion: This study is the first to calculate the burden of road traffic accidents in Nepal using Nepal's own data. Nepal needs to develop and enhance its own system to identify significant public health issues so as to set national priorities for prevention of road traffic accidents.